(Karakterisasi Listeria monocytogenes yang Diisolasi dari Pabrik Makanan Segar - MOORDIANI MOORDIANI; CATH REES; PHIL RICHARDS (Fakultas Farmasi Universitas Pancasila, 2014)
Listeria monocytogenes is a Gram positive rod-shape bacteria. Other foodborne pathogens, mostly, may cause typical symptoms of gastroenteritis. Unlike these microorganisms, Listeria monocytogenes infection may result in more serious symptoms, usually take in the form of meningitis or septicaemia. People with vulnerable immune system are in a bigger risk of being exposed. Furthermore, the bacterium is also severer than any other bacteria found in the food, with more resistant to heat, drying, or salty environment. This research was purposed to identify and characterize a sample named LM 25722248, which was isolated from fresh food factory in a city of United Kingdom. The isolate was characterized as a Gram positive bacterium, showed tumbling motility, and gave positive result for catalase test and haemolysin assay. Moreover, benefiting from molecular technology, it was possible to reveal that the isolate was Listeria monocytogenes.